MENINGKATKAN KEMAMPUAN GURU MIPA / IPS DI SMA N 1 KERAMBITAN DALAM MENYUSUN SILABUS DAN RPP YANG BERKARAKTER, MELALUI DISKUSI KELOMPOK TERFOKUS TAHUN PELAJARAN 2015/2016 - Nyoman Wardana (LP3M Universitas PGRI Mahadewa Indonesia, 2019)
This study aims to find out whether the focus group discussion method can improve the ability of PKN, Sociology, Economics and Natural Sciences teachers in Kerambitan 1 High School, Kerambitan District in preparing the Syllabus and Characterized Learning Implementation Plan (RPP). This type of research is a school action research (PTS) which consists of 2 (two) cycles. Each cycle consists of four stages: action planning, action implementation, observation and data collection, and reflection. The subjects of the study were PKN, Sociology, Economics and Natural Sciences teachers in SMA Negeri 1 Kerambitan, totaling 16 people consisting of 7 IPS group teachers and 9 science teachers. Data about the ability of MIPA teachers to compile syllabi and lesson plans was collected by the document study method. Then the data were analyzed descriptively. The results obtained from this study stated that: 1) the initial acquisition value of the syllabus was 62.56 with less categories at the beginning of Cycle I, increasing to 64.13 with enough categories at the end of Cycle I and being 71.63 with enough categories at the end of the Cycle II. 2) The initial ability to compile the RPP obtained a value of 61.81 with a less category, to 70.00 with enough categories at the end of Cycle 1 and to 73.00 with enough categories at the end of cycle II. The conclusion obtained from this study is that the focus group discussion method can improve the ability of MIPA teachers in Kerambitan 1 High School in preparing the Character Syllabus and Learning Implementation Plan (RPP).